2015
DOI: 10.7762/cnr.2015.4.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nursing Records and the Catholic Medical Center Nutritional Risk Screening as a Nutrition Screening Tool for Intensive Care Unit Patients

Abstract: In the present study, we aimed to compare the results from nutritional risk screening based on nursing records with those using the Catholic Medical Center Nutritional Risk Screening (CMCNRS) tool. A cross-sectional study was performed involving 91 patients aged ≥ 18 years from an intensive care unit. We collected general characteristics of the patients and nutrition screening was conducted for each patient by using computerized hospital program for the nursing records as well as the CMCNRS conducted by clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Our results are similar to the results of Heo et al (2015), which suggests that the agreement of the nurses' screening with that of the clinical dietitians' is a fair one (k= 0.243). Similar to our results of a significant difference in each of the questions of the NRS-2002, Heo et al (2015 reported highly significant difference (p<0.0001) for all subject indicators. Although our study lacked a control group and involved a single interdisciplinary educational intervention, improvements in both knowledge and practice were detected.…”
Section: Compared To the Dietitians'supporting
confidence: 87%
“…Our results are similar to the results of Heo et al (2015), which suggests that the agreement of the nurses' screening with that of the clinical dietitians' is a fair one (k= 0.243). Similar to our results of a significant difference in each of the questions of the NRS-2002, Heo et al (2015 reported highly significant difference (p<0.0001) for all subject indicators. Although our study lacked a control group and involved a single interdisciplinary educational intervention, improvements in both knowledge and practice were detected.…”
Section: Compared To the Dietitians'supporting
confidence: 87%